Hydrophobic interactions leading to a complex interplay between bioelectrocatalytic properties and multilayer meso-organization in layer-by-layer assemblies - Cortez, María Lorena (2014)
The present study explores the development of mesostructured bioelectrochemical interfaces with accurate compositional and topological control of the supramolecular architecture through the layer-by-layer assembly of ternary systems based on poly(allylamine) containing an osmium polypyridyl complex (OsPA), an anionic surfactant, sodium dodecyl sulfate (SDS) or sodium octodecyl sulfate (ODS), and glucose oxidase (GOx). We show that the introduction of the anionic surfactant allows a sensitive increase of the polyelectrolyte and the enzyme uptake at pH 7.0, enhancing its catalytic behavior in the presence of glucose as compared to the surfactant-free system (OsPA/GOx)n constructed at the same pH. Structural characterization of the multilayer films was performed by means of grazing-incidence small-angle X-ray scattering (GISAXS), which showed the formation of mesostructured domains within the composite assemblies. Experimental results indicate that the balance between ionic and hydrophobic interactions plays a leading role not only in the construction of the self-assembled system but also in the functional properties of the bioactive interface. The structure of the ternary multilayered films depends largely on the length of the alkyl chain of the surfactant. We show that surfactants incorporated into the film also play a role as chemical entities capable of tuning the hydrophobicity of the whole assembly. In this way, the deliberate introduction of short-range hydrophobic forces was exploited as an additional variable to manipulate the adsorption and coverage of protein during each assembly step. However, the integration of long-chain surfactants may lead to the formation of very well-organized interfacial architectures with poor electron transfer properties. This, in turn, leads to a complex trade-off between enzyme coverage and redox wiring that is governed by the meso-organization and the hydrophobic characteristics of the multilayer assembly.